2017
DOI: 10.1292/jvms.17-0018
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of cilostazol in a dog with sick sinus syndrome

Abstract: Sick sinus syndrome (SSS) is a type of bradyarrhythmia that can lead to syncope. Cilostazol has been reported to be an effective treatment for human patients with SSS and other bradyarrhythmias. This report describes the successful long-term treatment with cilostazol in a dog with SSS. A nine-year old intact male Miniature Schnauzer presented with a history of syncopal episodes and unsteady gait. After cilostazol treatment, the total heart rate (HR), mean HR, and frequency of premature ventricular contractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Recent studies have reported the effectiveness of orally administered cilostazol, a phosphodiesterase III inhibitor, in treating bradyarrhythmia in humans and animals [ 9 , 11 , 12 , 14 , 17 ]. Cilostazol is a platelet-aggregation inhibitor and has been administered intrinsically for preventing relapse in patients with cerebral infarction or chronic arterial occlusion.…”
mentioning
confidence: 99%
“…Recent studies have reported the effectiveness of orally administered cilostazol, a phosphodiesterase III inhibitor, in treating bradyarrhythmia in humans and animals [ 9 , 11 , 12 , 14 , 17 ]. Cilostazol is a platelet-aggregation inhibitor and has been administered intrinsically for preventing relapse in patients with cerebral infarction or chronic arterial occlusion.…”
mentioning
confidence: 99%
“…The dosages and timing of administration of cilostazol were selected based on past case reports ( 12 , 13 ), basic research ( 21 ), and the experience of the attending veterinarian. The most frequently used dose of cilostazol was 10.0–10.9 mg/kg twice daily (20.0–21.8 mg/kg/day).…”
Section: Resultsmentioning
confidence: 99%
“…Cilostazol, a phosphodiesterase III inhibitor, has recently been reported to be effective in the treatment of bradyarrhythmia in both humans ( 8 11 ) and animals [SSS ( 12 , 13 )]. Cilostazol is a platelet aggregation inhibitor that is used in humans to prevent recurrence of cerebral infarction or chronic arterial occlusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, cilostazol has been reported to increase the heart rate in healthy dogs, 15 and successfully treat sick sinus syndrome in a dog, the use of cilostazol has not been reported in cats. 16 The present study describes the clinical course and histological findings in a cat with high-grade AV block treated with cilostazol.…”
Section: Introductionmentioning
confidence: 93%